Risk of a post-colonoscopy colorectal cancer in patients with type 2 diabetes: a Danish population-based cohort study - Henrik Toft Sørensen; Lars Pedersen; Frederikke Schønfeldt Troelsen; Rune Erichsen (BMJ Open Gastroenterology)
Objective Prevalent type 2 diabetes (T2D) is associated with an increased risk of colorectal cancer and could impair the quality of bowel preparation for colonoscopy. This may in turn increase the risk of overlooked precancerous polyps and subsequent risk of post-colonoscopy colorectal cancer (PCCRC). We investigated whether patients with T2D are at increased risk of PCCRC compared with patients without T2D.Design We conducted a population-based cohort study of patients with T2D and without T2D undergoing colonoscopy in Denmark (1995–2015). We investigated the risk of PCCRC by calculating >6 to 36 months cumulative incidence proportions (CIPs) treating death and colectomy as competing risks. Using Cox proportional-hazards regression analyses, we also computed HRs of PCCRC, comparing patients with T2D and non-T2D. According to the World Endoscopy Organization guidelines, we calculated PCCRC 3-year rates to estimate the proportions of T2D and non-T2D CRC patients experiencing PCCRC.Results We identified 29 031 patients with T2D and 333 232 patients without T2D undergoing colonoscopy. We observed 250 PCCRCs among patients with T2D and 1658 PCCRCs among patients without T2D. The >6 to 36 months CIP after a first-time colonoscopy was 0.64% (95% CI 0.55% to 0.74%) for T2D and 0.36% (95% CI 0.34% to 0.38%) for patients without T2D. The HRs of PCCRC were 1.43 (95% CI 1.21 to 1.72) after a first-time colonoscopy and 1.18 (95% CI 0.75 to 1.85) after a second-time colonoscopy. The PCCRC 3-year rate was 7.9% for patients with T2D and 7.4% for patients without T2D.Conclusion T2D may be associated with an increased HR of PCCRC.